Thinking before sinning: reasoning processes in hedonic consumption - de Witt Huberts, Jessie; Evers, Catharine; de Ridder, Denise (Frontiers in Psychology, 2014)
Whereas hedonic consumption is often labelled as impulsive, findings from self-licensing research suggest that people sometimes rely on reasons to justify hedonic consumption. Although the concept of self-licensing assumes the involvement of reasoning processes, this has not been demonstrated explicitly. Two studies investigated whether people indeed rely on reasons to allow themselves a forbidden pleasure. Participants were exposed to a food temptation after which passive and active reasoning was assessed by asking participants to indicate the justifications that applied to them for indulging in that temptation (Study 1) or having them construe reasons to consume the hedonic product (Study 2). Regression analyses indicated that higher levels of temptation predicted the number of reasons employed and construed to justify consumption. By providing evidence for the involvement of reasoning processes, these findings support the assumption of self-licensing theory that temptations not only exert their influence by making us more impulsive, but can also facilitate gratification by triggering deliberative reasoning processes.